Adaptive pre-amplification pulse shaping in a high-power, coherently combined fiber laser system - Becker, Nils C.; Hadrich, Steffen; Eidam, Tino; Just, Florian; Osvay, Karoly; Varallyay, Zoltan; Limpert, Jens; Tunnermann, Andreas; Pertsch, Thomas; Eilenberger, Falk (Optics Letters, 2017)
We report on the successful implementation of an adaptive pre-amplification pulse shaping technique in a high-power, coherently combined fiber laser system to achieve sub-300-fs pulse durations at 320 W average power and 3.2 mJ pulse energy. The pulse shaper is utilized to impose a gain flattening mask to increase the spectral width of the amplified pulse by 60%. Simultaneously, it pre-compensates the spectral phase acquired in the multi-stage amplification and subsequent compression including the eight-channel, coherently combined main amplification stage. This result does significantly enhance the performance of the fiber laser system and the subsequent nonlinear compression stages.
CRIS-Team Scopus Importer:2023-04-20